2011
DOI: 10.1016/j.scitotenv.2011.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric concentrations and air–soil gas exchange of polycyclic aromatic hydrocarbons (PAHs) in remote, rural village and urban areas of Beijing–Tianjin region, North China

Abstract: Forty passive air samplers were deployed to study the occurrence of gas and particulate phase PAHs in remote, rural village and urban areas of Beijing–Tianjin region, North China for four seasons (spring, summer, fall and winter) from 2007 to 2008. The influence of emissions on the spatial distribution pattern of air PAH concentrations was addressed. In addition, the air–soil gas exchange of PAHs was studied using fugacity calculations. The median gaseous and particulate phase PAH concentrations were 222 ng/m3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(44 citation statements)
references
References 43 publications
4
38
1
Order By: Relevance
“…During this period, the observed PM 10 concentrations at all sites were among the lowest of the year. The scavenging effects of precipitation on atmospheric pollutants in northern China has also been demonstrated by other studies (Liu et al, 2008;Wang et al, 2011b). In summary, the seasonal variations of PM 10 concentrations are mainly affected by three factors: coal and biomass fuel combustion for heating in winter, sandstorms during the spring, and summer rain events.…”
Section: Seasonal Variation In Pm 10 Concentrationssupporting
confidence: 70%
See 3 more Smart Citations
“…During this period, the observed PM 10 concentrations at all sites were among the lowest of the year. The scavenging effects of precipitation on atmospheric pollutants in northern China has also been demonstrated by other studies (Liu et al, 2008;Wang et al, 2011b). In summary, the seasonal variations of PM 10 concentrations are mainly affected by three factors: coal and biomass fuel combustion for heating in winter, sandstorms during the spring, and summer rain events.…”
Section: Seasonal Variation In Pm 10 Concentrationssupporting
confidence: 70%
“…A similar phenomenon has been reported by Liu et al (2007), who conducted an extensive survey in the Northern China Plain during 2005e2006 and found that the concentrations of PAHs in ambient air in rural villages were similar to, even slightly higher than those in big cities. In a study of atmospheric PAHs in BeijingeTianjin area, no significant difference was found between rural villages and urban sites (Wang et al, 2011b). In fact, primarily due to the previous findings, rural village and rural field sites were designed separately in this study.…”
Section: Ambient Air Pm 10 Concentrationsmentioning
confidence: 83%
See 2 more Smart Citations
“…As an important matrix in urban terrestrial environment, soil has been a major sink of contaminates (Jones, 1994;Hippelein and Mclachlan, 1998;Manzetti, 2013) and well interacts with other environmental compartments. On the other hand, contaminated soil may also be a secondary emission source for some contaminates in the atmosphere (Jones, 1994;Hippelein and Mclachlan, 1998;Li et al, 2010;Wang et al, 2011b;Zhang et al, 2011b). Thus, investigations into the occurrence and soilair exchange of contaminates in soil can help to understand the fate of contaminates and impacts of anthropogenic activities on the environment under the backdrop of rapid urbanization.…”
Section: Introductionmentioning
confidence: 99%